The role of women in baroque society in Ricardo Palma’s Tradiciones peruanas - Ulloa Cavero, Ana María (2021)
In this paper we present the role of women in baroque society. In order to do this, we examine issues such as injustice towards women, the education they received and we mention two important female figures of the time, Sor Juana Inés de la Cruz and Ana Caro Mallén de Soto. Therefore, this text will be based on the stories «Al hombre por la palabra» and «Motín de limeñas» by Ricardo Palma, which will help us to contextualise the subject. The purpose of our work is to make the reader aware of our topic by providing information.